1997
DOI: 10.1046/j.1365-2273.1997.00895.x
|View full text |Cite
|
Sign up to set email alerts
|

Otological manifestations of primary ciliary dyskinesia

Abstract: Primary ciliary dyskinesia is a hereditary defect in the ultrastructure of cilia, leading to poor ciliary motility. The sinonasal and the bronchial manifestations of the disease are well documented; whereas its otological aspects have received less attention. In this report, we describe the clinical profile of 16 patients with primary ciliary dyskinesia laying particular emphasis on the otological manifestations. All children (11 patients) had bilateral otitis media with effusion. Of the five adults, three had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 0 publications
0
41
1
Order By: Relevance
“…Cilia within the eustachian tube are critically involved in clearance of normal secretions and abnormal fluids (5), and patients with primary ciliary dyskinesia or Kartagener syndrome have increased incidences of otitis media (29). Because Eya4 was expressed in eustachian tube mucociliary epithelia of newborn mice (Supplemental Figure 1C), we considered whether ciliary abnormalities contributed to otitis media in Eya4 -/-mice.…”
Section: Production Of Eya4-deficient Mice the Endogenous Eya4 Gene Wasmentioning
confidence: 99%
“…Cilia within the eustachian tube are critically involved in clearance of normal secretions and abnormal fluids (5), and patients with primary ciliary dyskinesia or Kartagener syndrome have increased incidences of otitis media (29). Because Eya4 was expressed in eustachian tube mucociliary epithelia of newborn mice (Supplemental Figure 1C), we considered whether ciliary abnormalities contributed to otitis media in Eya4 -/-mice.…”
Section: Production Of Eya4-deficient Mice the Endogenous Eya4 Gene Wasmentioning
confidence: 99%
“…All but 2 of the 8 papers identified [10,16] were published 10 years ago or more. The 8 papers reviewed comprise: 5 retrospective observational studies/case series [6,10,12,13,15], one cross-sectional study [11], one case report [16] and one letter in reply discussing 2 patients [14]. Four papers made conclusions recommending against the use of VT [6,10,12,15] and 2 papers were in favour of VT for OME in PCD patients [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies specifically assessed the natural history of 87 patients with OME and PCD [10,11]. Six papers reviewed the treatment of 81 patients with PCD and OME [6,[12][13][14][15][16]. All but 2 of the 8 papers identified [10,16] were published 10 years ago or more.…”
Section: Resultsmentioning
confidence: 99%
“…Kroon et al [16] pointed out that situs inversus can be found in 50% of PCD patients, whereas 23% of all patients with situs inversus have PCD. In 1997 El-Sayed et al [9] suggested that otitis media with eusion and conductive hearing loss should be considered as common sequelae in PCD patients. It was Van der Baan [37] who found a discrepancy between poor subjective middle ear complaints and objective middle ear performance in adult PCD patients.…”
Section: Clinical Featuresmentioning
confidence: 99%